2023
DOI: 10.1002/jpen.2506
|View full text |Cite
|
Sign up to set email alerts
|

The association between GLIM criteria–defined malnutrition and 2‐year unplanned hospital admission in outpatients with unintentional weight loss: A retrospective cohort study

Abstract: Background This study aimed to assess malnutrition using the Global Leadership Initiative on Malnutrition (GLIM) criteria and Subjective Global Assessment (SGA) at baseline and determine the GLIM criteria that best predicted unplanned hospitalization in outpatients with unintentional weight loss (UWL). Methods We performed a retrospective cohort study of 257 adult outpatients with UWL. The GLIM criteria and SGA agreement were reported using the Cohen kappa coefficient. Kaplan‐Meier survival curves and adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Because each individual must still meet a phenotypic criterion (weight loss, low BMI, or reduced muscle mass) to receive a diagnosis of malnutrition, 13–15 one cannot be diagnosed with malnutrition on the basis of meeting only an etiologic criterion. In general, the GLIM approach has had similar utility in identifying malnourished individuals and in predicting adverse outcomes as other approaches, such as SGA and AAIM 34–45 …”
Section: Resultsmentioning
confidence: 99%
“…Because each individual must still meet a phenotypic criterion (weight loss, low BMI, or reduced muscle mass) to receive a diagnosis of malnutrition, 13–15 one cannot be diagnosed with malnutrition on the basis of meeting only an etiologic criterion. In general, the GLIM approach has had similar utility in identifying malnourished individuals and in predicting adverse outcomes as other approaches, such as SGA and AAIM 34–45 …”
Section: Resultsmentioning
confidence: 99%
“…Good nutritional status is graded A, moderate malnutrition is graded B, and severe malnutrition is graded C ( 65 ). One study showed that SGA-rated malnutrition was associated with increased number of unplanned hospital admissions ( 66 ). Other studies have also implicated a correlation between malnutrition and mortality in cirrhotic patients assessed by SGA ( 1 , 67 ).…”
Section: Assessment Of Malnutritionmentioning
confidence: 99%
“…Malnutrition in acute and chronically ill citizens is associated with increased negative consequences for the individual patient and the society. Malnutrition has been associated with longer hospital stays, readmissions, depression, reduced quality of life, reduced physical ability, increased dependence on post-discharge care, among others [9][10][11][12][13][14][15]. These negative consequences pose a significant impact on the health economy.…”
Section: Frequency and Consequences Of Malnutrition And Nutritional Riskmentioning
confidence: 99%
“…Disease-related malnutrition (DRM) in acute and chronically ill citizens is associated with increased negative consequences for the individual as well as for the society due to increased economic cost [9][10][11][12][13][14][15]. DRM including nutritional risk has been investigated among inpatients and outpatients, but it is sparsely investigated in general practice among adult patients.…”
Section: Introductionmentioning
confidence: 99%